STRATEGIC RECOVERY AND ITS IMPACT ON ENHANCING STRATEGIC SOVEREIGNTY AN ANALYTICAL STUDY AT THE MINISTRY OF OIL/OIL EXPLORATION COMPANY - Batool Mohan Khader Al-Yasiri; Prof. Dr. Shehenaz Fadhil Ahmed (Scholars Digest Publishing, 2025)
The researchers aim through this study to identify the correlation and impact relationship between strategic recovery as an independent variable with its sub-dimensions (compensation, response speed, problem identification, positioning) and strategic dominance as a dependent variable with its dimensions (sphere of influence, competitive pressure, competitive structure, renewal). The researchers adopted the descriptive-analytical approach as a scientific method to analyze and interpret the study data. The questionnaire was used as the measurement tool for data and information collection, consisting of 40 items distributed to a purposive sample of 140 individuals representing the senior and middle management in the Oil Exploration Company. A total of 133 valid questionnaires were used for analysis. In addition, a set of direct questions was distributed to 14 decision-makers from the company under study. The researchers also relied on a set of approved statistical methods for data analysis, including "mean - standard deviation - Cronbach's alpha - factor analysis - skewness and kurtosis test - Pearson correlation coefficient - coefficient of determination (R²) - Z-test - T-test - F-test," using some ready-made statistical programs (SPSS V.28 - AMOS V.26 - Microsoft Excel V.2010). The study reached a number of findings, most notably the significant impact of strategic recovery on strategic dominance with its various dimensions. Therefore, adopting strategic recovery in the Oil Exploration Company is of great importance to influence the achievement of strategic dominance. The study concludes with a set of recommendations aimed at enhancing the company's strengths and addressing its weaknesses
Keywords: Strategic recovery, strategic sovereignty, Oil Exploration Company.